Open government data: critical information management perspectives. (15th January 2019) - Shepherd, Elizabeth; Bunn, Jenny; Flinn, Andrew; Lomas, Elizabeth; Sexton, Anna; Brimble, Sara; Chorley, Katherine; Harrison, Emma; Lowry, James; Page, Jessica
Abstract : Purpose: Open government data and access to public sector information is commonplace, yet little attention has focussed on the essential roles and responsibilities in practice of the information and records management professionals, who enable public authorities to deliver open data to citizens. This paper aims to consider the perspectives of open government and information practitioners in England on the procedural and policy implications of open data across local public authorities. Design/methodology/approach: Using four case studies from different parts of the public sector in England (local government, higher education, National Health Service and hospital trust), the research involved master's level students in the data collection and analysis, alongside academics, thus enhancing the learning experience of students. Findings: There was little consistency in the location of responsibility for open government data policy, the range of job roles involved or the organisational structures, policy and guidance in place to deliver this function. While this may reflect the organisational differences and professional concerns, it makes it difficult to share best practice. Central government policy encourages public bodies to make their data available for re-use. However, local practice is very variable and perhaps understandably responds more to local organisational strategic and resource priorities. The research found a lack of common metadata standards for open data, different choices about which data to open, problems of data redundancy, inconsistency and data integrity and a wide variety of views on the corporate and public benefits of open data. Research limitations/implications: The research is limited to England and to non-national public bodies and only draws data from a small number of case studies. Originality/value: The research contributes to the debate about emerging issues around the complexities of open government data and its public benefits, contributing to the discussions around technology-enabled approaches to citizen engagement and governance. It offers new insights into the interaction between open data and public policy objectives, drawing on the experience of local public sectors in England.